Evaluation of variability in subgrade loads - Porębski, Ryszard; Podagėlis, Igoris (Journal of Civil Engineering and Management, 2003)
The paper presents an analysis of variability in vertical stresses in the sleeper base. The research deals with the stresses caused by the track load by an ET 22 locomotive depending on the manner of pressure transfer by sleepers. Four schemes of force distribution under sleepers are being analysed. The research was carried out in Poznan Civil Engineering Institute. First Published Online: 26 Jul 2012